PROBLEMS IN TEACHING HIGHER MATHEMATICS TO NON-SPECIALIST STUDENTS - Пардаева ЗамираЎктамовна; Худойқулова Нигора Асилбек қизи (Scholars Digest Publishing, 2023)
Mathematics causes series problems for Non specialized education direction students. In this article scientific approach to these problems and their solutions is studied.
Keywords: Mathematics education, education problems, difficulties in teaching, mathematic knowledge.